Investigation on the origin of the magnetic moment of BiFeO3 thin films by advanced x-ray characterizations - RODE, KARSTEN (My University, 2006)
Single phase 001 -oriented BiFeO 3 BFO thin films grown by pulsed laser deposition can only be obtained in a narrow window of deposition pressure and temperature and have a low magnetic moment. Out of the stability window Fe- or Bi-rich impurity phases form, which has a strong impact on the physical and structural properties of the films, even for impurity concentrations hardly detectable by standard x-ray diffraction mea- surements. By using more sensitive tools such as x-ray absorption spectroscopy and x-ray magnetic circular dichroism and performing advanced x-ray diffraction characterization, we show that in nonoptimal conditions Fe forms ferrimagnetic -Fe 2 O 3 precipitates that are responsible for virtually all the ferromagnetic signal measured on such BFO films by standard magnetometry. This confirms that the BFO phase has a very low intrinsic moment that does not depend on strain. We also study the influence of film thickness on the nucleation of parasitic phases and find that epitaxial strain can stabilize the pure BFO phase in slightly overoxidizing growth conditions
PUBLISHED
Keywords: pulsed laser; pulsed laser